PENGARUH BAURAN PEMASARAN TERHADAP LOYALITAS PELANGGAN PADA APOTEK UHO KENDARI - Zainuddin, Muh Zabir; Manan, La Ode ABdul; Sahyunu, Sahyunu; HM, Suyuti; Lajaraia, Ridha Taurisma; Naim, Ifin (Sultra Journal of Economic and Business, 2022)
The purpose of this study was to examine and explain the effect of the marketing mix on customer loyalty at UHO Kendari pharmacy both partially and simultaneously. This research approach is quantitative by using survey method with explanatory survey design. Data was collected using an instrument in the form of a questionnaire. Sampling technique with non-probability sampling method. The type of non-probability sampling used is purposive sampling with judgment sampling with respondent criteria so that the sample in this study is 70 respondents. The analytical tool used is multiple linear regression. In managing data and drawing conclusions, the researchers used the SmartPLS program (Partial Least Square). The results showed that the product had a positive and significant effect on customer loyalty. Price has a positive and significant effect on customer loyalty. Place has a positive and significant effect on customer loyalty. Promotion has a positive and significant effect on customer loyalty. With a high enough R-Square value in influencing the independent variable on the dependent variable.